2004
DOI: 10.1152/ajpheart.01055.2003
|View full text |Cite
|
Sign up to set email alerts
|

Nicorandil induces late preconditioning against myocardial infarction in conscious rabbits

Abstract: Nicorandil has been shown to induce an infarct-limiting effect similar to that induced by the early phase of ischemic preconditioning (PC). The goals of this study were to determine whether nicorandil induces a delayed cardioprotection that is analogous to the late phase of ischemic PC and, if so, whether nicorandil-induced late PC is associated with upregulation of cardioprotective proteins. Chronically instrumented, conscious rabbits received vehicle (intravenous normal saline; control group, n = 10), nicora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 74 publications
(118 reference statements)
2
16
0
Order By: Relevance
“…We clearly demonstrated that oral administration of nicorandil significantly increased both COX-2 mRNA and protein, resulting in the increased synthesis of prostaglandin I 2 at 6 h after treatment. These results are comparable with an earlier report that intravenous infusion of nicorandil reduced cardiac infarction in rabbits after ischemia/reperfusion injury and was accompanied by an increase in COX-2 expression 24 h after infusion [9]. Moreover, induction of GATA-4 by nicorandil preceded COX-2 induction.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We clearly demonstrated that oral administration of nicorandil significantly increased both COX-2 mRNA and protein, resulting in the increased synthesis of prostaglandin I 2 at 6 h after treatment. These results are comparable with an earlier report that intravenous infusion of nicorandil reduced cardiac infarction in rabbits after ischemia/reperfusion injury and was accompanied by an increase in COX-2 expression 24 h after infusion [9]. Moreover, induction of GATA-4 by nicorandil preceded COX-2 induction.…”
Section: Discussionsupporting
confidence: 91%
“…Previous reports have indicated that Bcl-2 was upregulated in the myocardium of rabbits subjected to ischemia/reperfusion injury 24 h after dosing with nicorandil [9] and was upregulated by GATA-4 in doxorubicin-treated heart 24 h after doxorubicin treatment [17]. Furthermore, a recent report has indicated that nicorandil inhibited the doxorubicin-induced decrease in Bcl-2 expression [35], while our present data indicated no such effect of nicorandil at 1-6 h after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26,54,55 Although the opening of the K-ATP channels is related to classic or first-window preconditioning, it has also been reported that nicorandil treatment upregulates the expression of cyclooxygenase-2 and Bcl-2 in MI, resulting in delayed cardioprotection similar to that afforded by the late phase of ischemic preconditioning. 56 Reports indicate that intravenous nicorandil treatment ameliorates early functional and clinical problems in patients with AMI. Ito et al 45 investigated whether intravenous nicorandil (6 mg for 24 hours after a 4-mg bolus injection) followed by oral administration of nicorandil would exert beneficial effects on microvascular function and clinical outcomes in a prospective, single-center study including 81 patients with a first anterior AMI who received successful PCI within 12 hours after symptom onset.…”
Section: Nicorandilmentioning
confidence: 99%